ACTIVITIES OF TRACE-ELEMENTS IN SILICATE MELTS - Fraser, D (1975)
A theoretical model has been developed which describes the amphoteric character of oxides in silicate melts. This has been used to account for the increased stability of the higher oxidation states of altervalent trace elements in silicate melts with increasing basicity and to derive a general expression for the estimation of trace element activities in silicate melts. © 1975.